Progress Testing for Medical Students at the University of Auckland: Results from the First Year of Assessments. (January 2014) - Lillis, Steven; Yielder, Jill; Mogol, Vernon; O'Connor, Barbara; Bacal, Kira; Booth, Roger; Bagg, Warwick
Background: Progress testing is a method of assessing longitudinal progress of students using a single best answer format pitched at the standard of a newly graduated doctor. Aim: To evaluate the results of the first year of summative progress testing at the University of Auckland for Years 2 and 4 in 2013. SUBJECTS: Two cohorts of medical students from Years 2 and 4 of the Medical Program. Methods: A survey was administered to all involved students. Open text feedback was also sought. Psychometric data were collected on test performance, and indices of reliability and validity were calculated. Results: The three tests showed increased mean scores over time. Reliability of the assessments was uniformly high. There was good concurrent validity. Students believe that progress testing assists in integrating science with clinical knowledge and improve learning. Year 4 students reported improved knowledge retention and deeper understanding. Conclusion: Progress testing has been successfully introduced into the Faculty for two separate year cohorts and results have met expectations. Other year cohorts will be added incrementally. Recommendation: Key success factors for introducing progress testing are partnership with an experienced university, multiple and iterative briefings with staff and students as well as demonstrating the usefulness of progress testing by providing students with detailed feedback on performance.